2001
DOI: 10.1002/1097-0142(20010615)91:12<2294::aid-cncr1261>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent hypermethylation of multiple tumor-related genes in gastric carcinoma and adjacent normal tissues

Abstract: Eine nach innen gerichtete Carboxygruppe des hier gezeigten Cavitanden verändert die Dynamik der Stickstoffinversion von Gast‐Aminen sowie die Bindung über H‐Brücken und die Bewegung im Hohlraum. NMR‐Experimente belegen z. B., dass die Inversion von Ethylmethylisopropylamin nach Einschluss im Cavitanden um mehrere Größenordnungen langsamer ist als in Lösung.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
50
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(59 citation statements)
references
References 23 publications
7
50
2
Order By: Relevance
“…Inactivation of tumor suppressor genes has been known to contribute to the abnormal proliferation, transformation, and progression in human cancers. Aberrant promoter methylation of cancer-related key genes, such as p16, E-cadherin, TIMP-3, APC, THBS1, and hMLH1, has been observed frequently in gastric carcinoma (Kang et al, 2001;Leung et al, 2001). …”
supporting
confidence: 92%
“…Inactivation of tumor suppressor genes has been known to contribute to the abnormal proliferation, transformation, and progression in human cancers. Aberrant promoter methylation of cancer-related key genes, such as p16, E-cadherin, TIMP-3, APC, THBS1, and hMLH1, has been observed frequently in gastric carcinoma (Kang et al, 2001;Leung et al, 2001). …”
supporting
confidence: 92%
“…Concurrent methylation of multiple tumor-related genes has been detected in 20% of normal tissues adjacent to gastric carcinoma by Leung et al [83]. We have also shown concurrent methylation (CIMP-H) in 15% of IM but not in chronic gastritis or normal gastric mucosa using a panel of six genes/loci including p16, hMLH1 and four CpG islands (MINT1, MINT2, MINT25 and MINT31) [81].…”
Section: Determined the Methylation Frequency Of 12 Genes Including supporting
confidence: 70%
“…Similar to colorectal cancer, the presence of methylation of hMLH1 gene is strongly associated with loss of hMLH1 protein expression and MSI-H phenotype in gastric carcinomas [52,81,83]. In contrast to gastric carcinoma, methylation of hMLH1 genes in gastric precursor lesions appears to be less frequently associated with MSI-H phenotype and loss of hMLH1 protein expression [81].…”
Section: Epigenetic Alterations In Gastric Carci-nomamentioning
confidence: 99%
“…It is well known that the lack of E-cadherin plays an important role in the development of gastric cancer and EMT. Three mechanisms of gene deletion include mutation (25), methylation (26) and E-box in the promoter region (27,28). Results of a previous study have shown that KLF17 is a negative regulation of E-cadherin by binding the E-Box promoter in breast cancer.…”
Section: Discussionmentioning
confidence: 99%